BIOLOGICAL SIGNIFICANCE OF AGING AND DEATH - Maripjonov Jasurbek Ma’mirjon o’g’li; Mahammadjonova Fotima Tohirjon qizi; Mahammadjonova Zuhra Tohirjon qizi (Journals Park Publishing, 2025)
Aging is characterized by a gradual loss of physiological integrity, leading to functional decline and increased vulnerability to death. This deterioration is a primary risk factor for major human pathologies, including cancer, diabetes, cardiovascular diseases, and neurodegenerative disorders. Research on aging has seen unprecedented progress in recent years, particularly in understanding how the rate of aging is regulated by genetic pathways and biochemical processes that have been preserved at least to some extent through evolution.
Keywords: Genetic theories, cellular processes, disposable soma, biological significance of death.